Rekrutmen Talenta Global di BUMN Penerbangan Indonesia: Studi Kasus Pengangkatan Direksi Asing di PT Garuda Indonesia (Persero) Tbk dalam Perspektif Strategic Human Resource Management (SHRM) - Eliza Deis Widoputri; Indah Mustika Choirum; Raisa Ayu Rininta (Journal of Administration, Governance, and Political Issues, 2025)
Facing a persistent financial crisis and critical post-pandemic competency gaps, PT Garuda Indonesia (Persero) Tbk took a strategic step by recruiting two foreign nationals (FNs) to its board of directors in October 2025, supported by an amendment to the State-Owned Enterprise (SOE) Law. This decision is a manifestation of the external fit strategy within Strategic Human Resource Management (SHRM) to acquire specific expertise (financial turnaround and operational efficiency) that is scarce in the domestic market. This study analyzes the decision to appoint foreign directors as a response to the Global Talent Challenge and the challenge of institutional embeddedness. Data was obtained through a qualitative case study, in-depth interviews with Garuda Indonesia practitioners, and regulatory and media analysis. The decision is legally sound and demonstrates a meritocratic effort to overcome the competency gap. Findings show that integrating foreign leadership into the Indonesian SOE context requires more than just technical expertise. The acceptance of local human resources (overcoming in-group bias) is heavily determined by the foreign leadership's performance legitimacy and a conscious effort to implement a crossvergence culture (a blend of local values and global professionalism). To ensure long-term success and build domestic capacity, this strategy must be balanced with a global succession plan and a structured knowledge transfer system, ensuring foreign talent acts as a transformative catalyst. Garuda can achieve a win-win outcome by maintaining global competitiveness while strengthening local leadership.